A new synthetic derivative of cryptotanshinone KYZ3 as STAT3 inhibitor for triple-negative breast cancer therapy. Issue 11 (November 2018) - Zhang, Wenda; Yu, Wenying; Cai, Guiping; Zhu, Jiawen; Zhang, Chao; Li, Shanshan; Guo, Jianpeng; Yin, Guoping; Chen, Chen; Kong, Lingyi
Abstract Silencing STAT3 is confirmed as a promising therapeutic strategy for triple-negative breast cancer (TNBC) therapy to address the issue of its poor prognosis. In this study, the natural product cryptotanshinone was firstly remodeled and modified as a more effective STAT3 inhibitor by structure-based strategy. The synthetic derivativeKYZ3 had 22–24-fold increase in antitumor activity than cryptotanshinone on two TNBC cell lines but had little effect on normal breast epithelial MCF-10A cells. Further investigation showed thatKYZ3 inhibited persistent STAT3 phosphorylation. It also prevented the STAT3 protein nuclear translocation to regulate the expressions of the target oncogenes including Bax and Bcl-2. Furthermore, KYZ3 inhibited TNBC cell metastasis by decreasing the levels of MMP-9 which were directly regulated by activated STAT3. A STAT3 plasmid transfecting assay suggested thatKYZ3 induced tumor cell apoptosis mainly by targeting STAT3. Finally, KYZ3 suppressed the growth of tumors resulting from subcutaneous implantation of MDA-MB-231 cells in vivo. Taken together, KYZ3 may be a promising cancer therapeutic agent for TNBC.